REBORN. Retro-avant-garde in The Army of the Iliad by Leopoldo Lugones. 1908-1915 - Tobares, Javier (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2019)
This article constitutes the partial progress of a larger work that is under development in the context of our doctoral thesis Crossroads. The concept of people in the work of Leopoldo Lugones. 1910-1932 (FFyH, UNC, 2017). The commemoration of the Centennial of the May Revolution is the moment in which Lugones traces, from his perspective, the articulation of a discourse that sought to redefine the parameters of social and political organization. The four works in which he draws his project work as a retro-avant-garde resource in which time condenses into a past that refers –not without tensions– to classical Greece and projects Argentina to the future, from a present that is perceived as a situation of temporary emptiness, a (re) founding moment of a sociopolitical utopia. Thus, the tetralogy of the Centenary constitutes the point of reference from which Lugones compresses the time of his story, recovers the past and projects it into the future in El Ejército de la Iliada (1915).